Unreal reality - Lisitsina, Yana (project baikal, 2021)
It is impossible to study national art without understanding the experience of the previous generations of artists who worked in the frameworks of socialist realism, an art method prevailing in the Soviet area. This cultural phenomenon is characterized by idealization and transformation of the reality in compliance with the state ideology, and by the impact of artistic images on the collective consciousness. The author uses archive materials to study the case related to the portraits of stakhanovites of Eastern Siberia created by Irkutsk artists and the reaction from party structures.